Improved growth performance, food efficiency, and lysine availability in growing rats fed with lysine-biofortified rice - Qing-Qing Yang; Pui Kit Suen; Chang-Quan Zhang; Wan Sheung Mak; Ming-Hong Gu; Qiao-Quan Liu; Samuel Sai-Ming Sun (Scientific Reports)
Abstract Rice is an excellent source of protein, and has an adequate balance of amino acids with the exception of the essential amino acid lysine. By using a combined enhancement of lysine synthesis and suppression of its catabolism, we had produced two transgenic rice lines HFL1 and HFL2 (High Free Lysine) containing high concentration of free lysine. In this study, a 70-day rat feeding study was conducted to assess the nutritional value of two transgenic lines as compared with either their wild type (WT) or the WT rice supplemented with different concentrations of L-lysine. The results revealed that animal performance, including body weight, food intake, and food efficiency, was greater in the HFL groups than in the WT group. Moreover, the HFL diets had increased protein apparent digestibility, protein efficiency ratio, and lysine availability than the WT diet. Based on the linear relationship between dietary L-lysine concentrations and animal performance, it indicated that the biological indexes of the HFL groups were similar or better than that of the WT20 group, which was supplemented with L-lysine concentrations similar to those present in the HFL diets. Therefore, lysine-biofortified rice contributed to improved growth performance, food efficiency, and lysine availability in growing rats.